Prevalence of Some Parasitic Infections in Iraq from 2019 to 2020 - Bedair, Nada Hassan; Zeki, Israa Naif (Iraqi Journal of Science, 2023)
Parasitic infections are associated with low education, wars and migration, absence of animal control and poor sanitation. Infections like visceral and cutaneous leishmaniasis (VL and CL), trichomoniasis, toxoplasmosis, malaria, echinococcosis and schistosomiasis are all spread worldwide and have harmful effects on individuals and societies. The aim of this survey was to identify the possible association of these infections with spatial distribution (province/governorate) and patient demographics (age and gender). According to the data collected from the Iraqi National CDC from 2019 to 2020, the predominant parasitic infections in both years were trichomoniasis and CL, followed by echinococcosis, VL and toxoplasmosis. Iraq is malaria and schistosomiasis free. The highest incidence rate of trichomoniasis was in Duhouk (2019) and Al-Dewaniya (2020) and majority of CL cases were in Diala in both 2019 and 2020. The number of echinococcosis cases was the highest in Thi-Qar (2019) and in Nineveh (2020). VL mostly affected Al-Dewaniya (2019) and Thi-Qar (2020). Toxoplasmosis scored the highest incidence rate in Basra in 2019 and 2020. All infections were higher in 2019 than in 2020, except for CL. As for age groups: echinococcosis, toxoplasmosis and trichomoniasis were higher in age group 15 – 44 years, while VL and CL was most common in 0-14 years juveniles in both years. Females were more affected than males by echinococcosis, toxoplasmosis, and trichomoniasis, while VL and CL affected males more often in the years included in this study.